Akreditasi:Pengaruhnya Terhadap Program Hand Hygiene Di Rumah Sakit Muhammadiyah Cirebon - Ari Nurfikri; Triana Karnadipa (Jurnal Sosial Humaniora Terapan, 2020)
This study aims to measure the implementation of the hand hygiene program at the Muhammadiyah Hospital Cirebon after accreditation. The method used is a qualitative analysis method, with a case study design. The research case is the Infection Control Prevention Working Group in which there is a hand hygiene program at the time of accreditation, including those that do not meet the minimum passing score, so the hand hygiene program implementation will be measured from an effective strategy, organizational characteristics, influence of the behavior of officers and patients and their families, and budget support from post accreditation management. The research instrument used interview guides with 4 respondents. The results of this study indicate that the Muhammadiyah Hospital in Cirebon does not yet have an effective strategy in building a hand hygiene culture. The post-accreditation Infection Control Prevention Team Organization is not running, so a hand hygiene program has not been established at the Muhammadiyah Hospital in Cirebon. The behavior of officers and patients the level of compliance with handwashing is still lacking, due to the use of consumables after accreditation is still low. In terms of the budget, the hospital has a good financial condition, but because there is no work program, the proposed expenditure budget of each unit does not reflect the need for programs that include training, procurement of consumables, and education for both officers and patients. ineffective hand hygiene strategies, PPI Committee organizational structure is not going well, there has been no change in hand hygiene behavior of employees, patients and visitors, and the PPI Committee budget is still contained in the unit budget, has not become a special budget item.Keyword: Hospital accreditation; cost; hand hygiene